The theory behind and factors influencing the use of telemedicine during the COVID‑19 pandemic: A systematic review - Arif Kurniawan; Elviera Gamelia; Dian Anandari (AOSIS, 2023)
A paradigm change in patient health care toward telemedicine services was necessary in 2020 due to the COVID‑19 pandemic, which broke out at the end of 2019. Theories used in determining the determinants of telemedi‑ cine utilization are various theories. Research conducted on the use of telemedicine still has doubts about the basic theory used in analyzing the factors that influence telemedicine, especially during the Covid‑19 pandemic. The goal of this study is to outline the fundamental principles of telemedicine utilization during the Covid‑19 outbreak and the variables that affect it. This Literature Review uses the scoping review method with the tool procedure, namely PRISMA. Based on the conducted literature review, there are 12 scholarly papers addressing the variables that affect the utilization of telemedi‑ cine services. During the Covid 19 epidemic, more individuals in many nations used telemedicine services. Anderson's theory of health care use and the idea of technology adoption or acceptance serve as the foundational theories for forecasting the variables that affect the use of telemedicine. The utiliza‑ tion of telemedicine is influenced by 29 different factors that come from different theories. The desire for health, exposure to COVID 19, co‑morbidities, social media usage, avoiding contamination, time efficiency, ease of use of services, social impact, and hedonic incentive are among the factors associ‑ ated to the COVID 19 pandemic.